ROS Responsive Nanoplatform with Two‐Photon AIE Imaging for Atherosclerosis Diagnosis and "Two‐Pronged" Therapy. Issue 45 (20th October 2020) - Ma, Boxuan; Xu, Hong; Zhuang, Weihua; Wang, Yanan; Li, Gaocan; Wang, Yunbing
Abstract: Atherosclerosis, characterized by endothelial injury, progressive inflammation, and lipid deposition, can cause cardiovascular diseases. Although conventional anti‐inflammatory drugs reveal a certain amount of therapeutic effect, more reasonable design on plaque targeting, local anti‐inflammation, and lipid removal are still required for comprehensive atherosclerosis therapy. In this work, a theranostic nanoplatform is developed for atherosclerosis recognition and inhibition. A two‐photon aggregation‐induced emission (AIE) active fluorophore (TP) developed is linked to β‐cyclodextrin (CD) with a ROS responsive bond, which can carry prednisolone (Pred) in its entocoele via supramolecular interaction to build a diagnosis‐therapy compound two‐photon fluorophore‐cyclodextrin/prednisolone complexes (TPCDP). With TPCDP packaged by nanosized micelles based on a ROS sensitive copolymer poly (2‐methylthio ethanol methacrylate)‐poly (2‐methacryloyloxyethyl phosphorylcholine), the TPCDP@PMM can accumulate in atherosclerotic tissue through the damaged vascular endothelium. Activated by the local overexpressed ROS and rich lipid, the micelles are interrupted and TPCDP is further disintegrated with Pred release due to the relatively stronger interaction of lipid with CD, resulting in anti‐inflammatory activity and lipid removal for atherosclerosis inhibition. Besides, labeled with the TP, TPCDP@PMM indicates a distinct two‐photon AIE imaging on atherosclerosis recognition. The "two‐pronged" therapeutic effect and plaque location ability has been confirmed in vivo on ApoE −/− mice, holding TPCDP@PMM a great promise for atherosclerosis theranostics. Abstract : A theranostic nanoplatform two‐photon fluorophore‐cyclodextrin/prednisolone complexes loaded with poly (2‐methylthio ethanol methacrylate)‐poly (2‐methacryloyloxyethyl phosphorylcholine) (TPCDP@PMM) is constructed with reactive oxygen species (ROS) responsive and two‐photon aggregation‐induced emission (AIE) bioimaging, which can realize the ROS triggered prednisolone delivery for anti‐inflammation, local lipid removal, and plaques recognition. Thereby, TPCDP@PMM demonstrates a great potential for clinical atherosclerotic diagnosis and "two‐pronged" therapy.